2021
DOI: 10.1101/2021.10.13.460524
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Networks of common inputs to motor neurons of the lower limb reveal neural synergies that only partly overlap with muscle innervation

Abstract: Movements are reportedly controlled through the combination of synergies that generate specific motor outputs by imposing an activation pattern on a group of muscles. To date, the smallest unit of analysis has been the muscle through the measurement of its activation. However, the muscle is not the lowest neural level of movement control. In this human study, we identified the common synaptic inputs received by motor neurons during an isometric multi-joint task. We decoded the spiking activities of dozens of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 40 publications
4
12
0
Order By: Relevance
“…Our findings of complex hierarchically-structured network interactions of muscle fibers across topologically distant leg and back muscles align with recent works investigating motor neuron recruitment during exercise and inter-muscular coherence (Hug et al, 2021), which demonstrated that motor neurons from distant muscles (e.g., hamstrings and gastrocnemii) may receive common neuronal input during dynamic pedaling. Other works have reported the presence of common neural inputs also to other pairs of distinct muscles such as hamstrings and plantar flexors (Hug et al, 2011), as well as glutei and quadriceps during gait (Dominici et al, 2011).…”
Section: Discussionsupporting
confidence: 90%
“…Our findings of complex hierarchically-structured network interactions of muscle fibers across topologically distant leg and back muscles align with recent works investigating motor neuron recruitment during exercise and inter-muscular coherence (Hug et al, 2021), which demonstrated that motor neurons from distant muscles (e.g., hamstrings and gastrocnemii) may receive common neuronal input during dynamic pedaling. Other works have reported the presence of common neural inputs also to other pairs of distinct muscles such as hamstrings and plantar flexors (Hug et al, 2011), as well as glutei and quadriceps during gait (Dominici et al, 2011).…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, evidence that beta (13-30 Hz) activity in EEG over sensorimotor cortex underlies and reflects muscle synergies (Aumann & Prut, 2015) suggests that it might be possible to detect the initial and ongoing interactions among the new and old heksors. These studies might also incorporate parallel analyses of the spinal motoneuron synergies recently hypothesized by Hug et al (2021). Once again, a video game format in which the participants control EMG activity in specific muscles (or EMG produced by specific groups of motoneurons) could be useful.…”
Section: Evaluating the Wider Applicability Of The New Conceptsmentioning
confidence: 99%
“…These studies might also incorporate parallel analyses of the spinal motoneuron synergies recently hypothesized by Hug et al. (2021). Once again, a video game format in which the participants control EMG activity in specific muscles (or EMG produced by specific groups of motoneurons) could be useful.…”
Section: Introductionmentioning
confidence: 99%
“…To account for the fact that the strength of common synaptic inputs between two motor neurons is not proportional to the degree of correlation between their outputs (de la Rocha et al ., 2007), we only interpreted the correlation coefficients based on their significance (Hug et al ., 2021b). Specifically, we defined a significance threshold as the 95 th percentile of the cross-correlation coefficient distribution generated with resampled versions of the motor unit spike trains.…”
Section: Methodsmentioning
confidence: 99%